Crescimento, acúmulo de macronutrientes e adubação fosfatada de alho nobre em região de altitude no semiárido - Silva, Otaciana Maria dos Prazeres da (Universidade Federal Rural do Semi-Árido, 2019)
The expansion of garlic production to new area of cultivation promote productivity increases, however, the plants will be influenced by the local soil's climatic conditions, requiring an adaptation of the management techniques used in the crop, like phosphate fertilization. The objective of this research was to evaluate the effect of phosphorus doses on the growth, nutrient accumulation and productivity of the noble garlic cultivated in the semi-arid region. The work was conducted in the Municipality of Portalegre, RN, from June to September 2017. A complete randomized complete block design with four replications was used. In the growth and nutrient accumulation evaluations, the treatments were arranged in subdivided parcel. The parcels were composed of phosphorus doses: 0, 60, 120, 180 and 240 kg ha-1. The subplots were formed by plant sampling times (30, 40, 50, 60, 70, 80 and 90 days after planting). Leaf area, dry matter of aerial part, bulb and total, bulbar ratio, leaf area ratio, absolute growth rate, relative growth rate and net assimilation rate were determined. The accumulations of N, P, K, Ca and Mg of aerial part, bulb and total. For the production evaluations, the treatments were constituted by doses of phosphorus: 0, 60, 120, 180 and 240 kg ha-1. Height of plants, number of leaves; cycle, final stand; average mass of bulbs; percentage of superbroke; total commercial and non-commercial productivity of bulbs; number of bulbs per bulb; classification of bulbs and bulbs, and the dose of maximum economic efficiency were assessed. The maximum leaf area of the garlic plants was obtained with the dose of 180 kg ha-1 of phosphorus. The highest rates of relative growth and net assimilation rate were obtained at 40 days after planting. The highest accumulation of bulb dry matter and total, and absolute growth rate, occurred at the end of the garlic crop cycle. From the 70 days after planting, the higher doses of P promoted the highest total accumulations of macronutrients in the garlic plants, obtained at the end of the crop cycle. The accumulation of macronutrients accompanied the growth of garlic plants with extraction order: N> K> Ca> P> Mg, with N, P and K being the most accumulated in the bulbs, while Ca and Mg in the leaves. The emergence and height of plants, final stand, non-commercial bulbs and number of bulbs per bulb were not influenced by phosphorus doses. The highest mean bulb mass and total bulb yield were obtained at the 176 and 182 kg ha-1 doses of P, respectively. The maximum economic efficiency dose was 165 kg ha-1 of P, which promoted higher productivity of commercial bulbs (6.69 t ha-1)
Keywords: Allium sativum L; Análise de crescimento; Acúmulo de nutrientes; Produtividade; Allium sativum L; Growth analysis; Accumulation of nutrients; Productivity; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA